2013
DOI: 10.1089/aid.2012.0200
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cell Number and Responses to Toll-Like Receptor 7 and 9 Agonists Vary in HIV Type 1-Infected Individuals in Relation to Clinical State

Abstract: In HIV-1 infection, plasmacytoid dendritic cell (PDC) numbers and function are decreased. No detailed comparisons of PDC responses to various stimuli in HIV-1-infected patients are available. Using for the first time purified PDCs, we compared PDC responses [interferon (IFN)-a production/cell] to various stimuli in a large number (n = 48) of HIV-1-infected patients and healthy volunteers (n = 19). Toll-like receptor (TLR)7-and TLR9-induced expression of PDC surface activation and maturation markers was also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
4
17
1
Order By: Relevance
“…No associations between DC percentages and CD4 + T-cell counts were found. This contradicts previous studies that reported a positive correlation between DC numbers with CD4 + T-cell counts in untreated and treated chronically HIV-infected individuals [5,41,42], patients with primary HIV infection [15], a cohort comprising HIV and HIV/HCV coinfected patients [24] and in a longitudinal study that followed HIV-infected patients during 60 weeks of ART [40]. The absence of a correlation probably reflects selection bias as all participants in our study started ART with CD4 + T-cell counts <200 cells/L, whereas prior cross-sectional studies included patients with a wider range of baseline CD4 + T-cell counts.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…No associations between DC percentages and CD4 + T-cell counts were found. This contradicts previous studies that reported a positive correlation between DC numbers with CD4 + T-cell counts in untreated and treated chronically HIV-infected individuals [5,41,42], patients with primary HIV infection [15], a cohort comprising HIV and HIV/HCV coinfected patients [24] and in a longitudinal study that followed HIV-infected patients during 60 weeks of ART [40]. The absence of a correlation probably reflects selection bias as all participants in our study started ART with CD4 + T-cell counts <200 cells/L, whereas prior cross-sectional studies included patients with a wider range of baseline CD4 + T-cell counts.…”
Section: Discussioncontrasting
confidence: 97%
“…Our data showing an inverse association between DC frequencies and HIV viral loads is consistent with previous studies [15,41,42] and is consistent with a role for DC in the control of HIV replication. This may involve the antiviral cytokine, IFN, present at higher levels in HIV controllers than viremic patients [43].…”
Section: Discussionsupporting
confidence: 93%
“…Many cancers, autoimmune disorders, and chronic infections are associated with decreased responsiveness of pDCs to TLR agonists (5,(11)(12)(13)(14). This dysfunction of the pDC response is well documented in the context of HIV type 1 infection (15)(16)(17)(18)(19)(20)(21). The role of pDCs during HIV infection is complex and not fully understood (5,7).…”
mentioning
confidence: 99%
“…Diminished levels and dysfunctional dendritic cells (DCs) are also frequently observed and may contribute to an overall impairment of adaptive immunity (6)(7)(8).…”
Section: Aids Progression Is Characterized By Depletion and Functionamentioning
confidence: 99%